Kolaborasi Pemerintah Desa dan BUMDes dalam Program Ketahanan Pangan di Desa Tubu, Kecamatan Bikomi Nilulat - Egidius Fkun; Ahariana Rihi; Yosef Kristoforus Taekab (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
This study aims to analyze the collaboration between the village government and the Village-Owned Enterprise (BUMDes) in implementing the food security program in Tubu Village, Bikomi Nilulat Subdistrict, North Central Timor Regency. This study is motivated by the importance of food security, particularly in border areas that face limitations in resources and economic access. The research uses a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving village officials, BUMDes managers, and community members. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The analysis framework refers to collaborative management theory, which includes direct dialogue, trust building, commitment to the process, and shared understanding. The results show that collaboration between the village government and BUMDes has been implemented but has not yet been optimal. Direct communication has occurred but is not carried out consistently; trust among stakeholders remains constrained by limited transparency and coordination; commitment to program implementation requires strengthening through active participation and sustainability efforts; and shared understanding of program objectives still needs improvement. This study concludes that strengthening collaboration through improved communication, transparency, human resource capacity, and joint commitment is essential to ensure the sustainability of food security programs and enhance community welfare.